Membangun Daya Saing dan Talenta Koperasi dengan Mengoptimalkan Potensi Internal dan Eksternal dalam Pengembangan Koperasi Berkelanjutan - Indra Fahmi (LPPM Universitas Koperasi Indonesia, 2025)
Cooperatives in Indonesia have a strategic contribution to the national economy. However, cooperatives face challenges in the form of limited competent human resources (HR) and relevance in an increasingly competitive economic ecosystem. This article discusses inside-out and outside-in approaches in optimizing internal and external cooperative drivers, including humanresource development, financial management, technology adaptation, and external collaboration. By implementing these strategies, cooperatives are expected to be able to increase competitiveness and sustainability in the modern market.